KINETICS, DIFFUSIVITY COEFFICIENT AND ANTHOCYANIN CONTENT IN OSMOTIC DEHYDRATION OF RASPBERRY HERITAGE (RUBUS IDAEUS) - Elías Silupu, Jorge Wilmer (2019)
The fruit of raspberry (Rubus idaeus) is widelyknown as strawberry of the forest but very littleused industrially. In this sense, the objective of theresearch work was to determine the influence ofsucrose concentration and anthocyanin contenton raspberry osmotic dehydration, for which theeffective diffusivity coefficient was calculated usingthe Crank model. Consequently, we worked with aresearch design of 2 concentration levels (50 and60 ° Brix) with 3 temperature levels (40, 50 and 60° C) analyzing all the samples in triplicate, being themaximum value of loss of weight and loss of waterworking at a temperature of 60 ° C and concentrationof 60 ° Brix, also the highest level of gain of solublesolids was studying at a temperature of 60 ° C andconcentration of 50 ° Brix. On the other hand, themaximum value calculated for the effective diffusivityof sucrose was 4.05E-10 m2 / s for a n = 1 comparingat a temperature of 40 ° C and a concentration of 50 °Brix. It should be noted that the anthocyanin contentwas determined when the raspberry reached itsosmotic equilibrium, registering the maximum valueof the anthocyanin content of 67.42 mg cyanidine-3glucoside / 100 gr of sample at a temperature of40 ° C with a concentration of 50 ° Brix. Finally, theanalysis of variance with P-values less than 0.05shows a significant effect between the concentrationfactors of sucrose and temperature on the kineticsof osmotic dehydration with a 95% confidence level.